Aryl hydrocarbon receptor: The master regulator of immune responses in allergic diseases - Riaz, Farooq; Pan, Fan; Wei, Ping (Frontiers in Immunology, 2022)
The aryl hydrocarbon receptor (AhR) is a widely studied ligand-activated cytosolic transcriptional factor that has been associated with the initiation and progression of various diseases, including autoimmune diseases, cancers, metabolic syndromes, and allergies. Generally, AhR responds and binds to environmental toxins/ligands, dietary ligands, and allergens to regulate toxicological, biological, cellular responses. In a canonical signaling manner, activation of AhR is responsible for the increase in cytochrome P450 enzymes which help individuals to degrade and metabolize these environmental toxins and ligands. However, canonical signaling cannot be applied to all the effects mediated by AhR. Recent findings indicate that activation of AhR signaling also interacts with some non-canonical factors like Kruppel-like-factor-6 (KLF6) or estrogen-receptor-alpha (Erα) to affect the expression of downstream genes. Meanwhile, enormous research has been conducted to evaluate the effect of AhR signaling on innate and adaptive immunity. It has been shown that AhR exerts numerous effects on mast cells, B cells, macrophages, antigen-presenting cells (APCs), Th1/Th2 cell balance, Th17, and regulatory T cells, thus, playing a significant role in allergens-induced diseases. This review discussed how AhR mediates immune responses in allergic diseases. Meanwhile, we believe that understanding the role of AhR in immune responses will enhance our knowledge of AhR-mediated immune regulation in allergic diseases. Also, it will help researchers to understand the role of AhR in regulating immune responses in autoimmune diseases, cancers, metabolic syndromes, and infectious diseases.